2020
DOI: 10.3390/cancers12092519
|View full text |Cite
|
Sign up to set email alerts
|

Definition and Independent Validation of a Proteomic-Classifier in Ovarian Cancer

Abstract: Mass-spectrometry-based analyses have identified a variety of candidate protein biomarkers that might be crucial for epithelial ovarian cancer (EOC) development and therapy response. Comprehensive validation studies of the biological and clinical implications of proteomics are needed to advance them toward clinical use. Using the Deep MALDI method of mass spectrometry, we developed and independently validated (development cohort: n = 199, validation cohort: n = 135) a blood-based proteomic classifier, stratify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…As detailed below, we find better reproducibility when we include information from both the fine structure and the bumps when determining the feature values for each peak. To maintain a consistent naming convention used in previously published literature [6,7,[11][12][13][14][15], we will use the general term "feature" to refer to the peaks and "feature value" to be the semiquantitative numerical value we calculate to represent the relative abundance of that feature (protein or peptide) within the sample. High-resolution images of a representative unprocessed and processed MALDI-TOF spectrum across the entire acquisition range (m/z = 3 to 30 kDa) is shown in the Supplementary Materials Figure S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As detailed below, we find better reproducibility when we include information from both the fine structure and the bumps when determining the feature values for each peak. To maintain a consistent naming convention used in previously published literature [6,7,[11][12][13][14][15], we will use the general term "feature" to refer to the peaks and "feature value" to be the semiquantitative numerical value we calculate to represent the relative abundance of that feature (protein or peptide) within the sample. High-resolution images of a representative unprocessed and processed MALDI-TOF spectrum across the entire acquisition range (m/z = 3 to 30 kDa) is shown in the Supplementary Materials Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…These highly multiplexed data can be combined into diagnostic tests using machine learning techniques designed to work well in the clinical setting where we generally have more attributes than samples, without overfitting [7,8]. Multiple tests in the area of oncology were developed using this approach [9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…It has already been observed that certain ML architectures facilitate SV calculations, e.g., tree SHAP [ 14 ]. The additive axioms satisfied by SVs facilitate SV calculations for tests based on ensemble averages, and ML methods based on regularized combinations of small coalitions of features also present the possibilities of exact SV calculations for tests which include large numbers of features [ 36 39 ]. Systematic studies of the convergence of sampling-based approximations to exact SV calculations for models with these architectures are underway.…”
Section: Discussionmentioning
confidence: 99%